The effectiveness of various biological control agents on blister blight disease (Exobasidium vexans Massee) on tea - Dini Jamia Rayati (Jurnal Penelitian Teh dan Kina, 2011)
In order to obtain an effective, efficient, and environmentally sound biological control method of blister blight disease (Exobasidium vexans Massee) on tea, a field trial has been conducted to know the effectiveness of various antagonistic microorganisms as biological control agents, on blister blight disease. The trial was carried out at Ciliwung Tea Plantation (1.400 m asl), Bogor, West Java, designed in randomized complete block (RCB), with 7 treatments and 3 replications. The treatments tested comprised 2 filamentous fungi (molds): Verticillium sp. and JD (unidentified); yeast: Rhodotorula rubra; 2 bacteria: B5 (unidentified) and Bacillus subtilis; copper-chemical fungicide as a standard treatment; and control. The biological control agents and fungicide were sprayed on tea bushes infected by blister blight disease, and the parameter observed was blister blight disease intensity, which was formulated in percentage of disease intensity index (DII). The results showed that in heavy-attack condition (disease intensity index higher than 50%), only yeast Rhodotorula rubra which was effective in suppressing blister blight disease intensity on tea, up to 22%. Meanwhile, the others treatments of antagonistic microorganisms could not suppress the disease intensity, even the copper-chemical fungicide as a standard treatment was no longer effective too.